A qualitative interview study with parents to identify barriers and drivers to childhood vaccination and inform public health interventions. Issue 9 (2nd September 2021) - Musa, Sanjin; Kulo, Aida; Bach Habersaat, Katrine; Skrijelj, Venesa; Smjecanin, Mirsad; Jackson, Cath
ABSTRACT: Vaccination coverage in the Federation of Bosnia and Herzegovina, in Bosnia and Herzegovina, has been declining since 2014. This qualitative study aimed to identify barriers and drivers to childhood vaccination for parents. The COM-B (capability-opportunity-motivation-behavior) model was the underpinning theoretical framework. Face-to-face interviews with 22 parents of fully (n = 6), delayed/partially vaccinated (n = 9) and unvaccinated (n = 7) children were conducted. Interviews explored individual factors (capability–knowledge and skills; motivation–attitudes, confidence and trust) and context factors (physical opportunity–information, access, health systems; and social opportunity – social support, norms). Data were analyzed in NVivo using content analysis exploring differences in COM factors by vaccination status and location. Parents of fully vaccinated children typically reported individual and context drivers to vaccination. They accepted vaccination, trusted health workers, and were content with services. Parents of delayed/partially vaccinated children fell into two subgroups: (1) Those who accepted vaccination and attributed delays to their organizational skills or frustration with appointment times. (2) Those fitting the profile of "vaccine hesitant" – generally valuing vaccination and health worker advice, yet with concerns often triggered by media/social media. Parents of unvaccinated children mentioned individual and context barriers to vaccination, notably significant concerns about safety, some distrust of health workers and resentment of mandatory vaccination. Urban/rural differences included urban parents being more likely to report experiences with vaccine shortages and very few had received information leaflets. The study identified complex and inter-related barriers and drivers to parents' childhood vaccination behaviors. These insights have informed the development of tailored interventions to improve coverage.